Emotional intelligence - creating a new roadmap for artificial intelligence. (17th December 2021) - Dey, Sharmistha; Chakraborty, Chinmay
Artificial intelligence (AI) changing the world with the power of creating intelligent solutions capable of autonomous decision-making and self-diagnostic abilities. Recent research on AI tends towards the use of emotional intelligence in artificial systems. A clear understanding of human emotion or cognitive behaviour can help an artificial system to become more rational and unbiased while making any decision. If a machine can think or feel like a human, it can be converted into a better decision-making system. This paper has performed a thorough review of state-of-the-art technologies and researches going in this particular field and tries to find out the current roadmap as well as the future trends in this area. This paper presents several types of research that are going on in this area and future trends.